FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PEMENUHAN KEBUTUHAN PENYULUH AGAMA DI PROVINSI JAWA BARAT - M. Taufik Hidayatullah; Pudji Muljono; Makmun Sarma; Darwis S Gani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
The research gets down the factors that effect the needs compliance level of religion counselor. The research is occurred between September and November 2012 in West Java province. Religion counselor is the object of the research. After census research has been through, the complete questionnaire from 114 correspondents are able to processed for the need of analysis. The analysis that is used is Path Analysis. The result depicts more than half of correspondents have high needs compliance level either the whole of it or part of it in every research region, and some factors are also affecting the needs compliance level of religion counselor.